2014
DOI: 10.9758/cpn.2014.12.2.75
|View full text |Cite
|
Sign up to set email alerts
|

Anti-dementia Activity of Nobiletin, a Citrus Flavonoid: A Review of Animal Studies

Abstract: Alzheimer's disease (AD), the most common form of dementia among the elderly, is characterized by the progressive decline of cognitive function and has a detrimental impact worldwide. Despite intensive laboratory and clinical research over the last three decades, pharmacological options for the prevention and effective long-term treatment of AD are not currently available. Consequently, successful therapeutic and preventive treatments for AD are needed. When researching materials from natural resources having … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 76 publications
(95 reference statements)
2
42
0
Order By: Relevance
“…Nobiletin is an O-methylated flavonoid present in citrus peels, with an empirical formula of C 21 H 22 O 8 and a molecular weight of 402.39, which has been reported to possess anti-inflammatory and antioxidant properties (8)(9)(10). Previous studies have reported that nobiletin may protect against cisplatin-induced acute kidney injury by preserving renal function and restoring antioxidant status (11).…”
Section: Introductionmentioning
confidence: 99%
“…Nobiletin is an O-methylated flavonoid present in citrus peels, with an empirical formula of C 21 H 22 O 8 and a molecular weight of 402.39, which has been reported to possess anti-inflammatory and antioxidant properties (8)(9)(10). Previous studies have reported that nobiletin may protect against cisplatin-induced acute kidney injury by preserving renal function and restoring antioxidant status (11).…”
Section: Introductionmentioning
confidence: 99%
“…Nobiletin (Fig. 1) is a type of polymethoxyflavonoid, which is predominantly found in Pericarpium Citri Reticulatae, a traditional Chinese medicine (9). Nobiletin exists in the pericarp of citrus fruits, and exerts extensive physiological effects that are beneficial to health.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the effect of nobiletin on the uncoupling proteins may be mediated by mitochondrial protein kinase A (PKA). It has been found that nobiletin via cytoplasmic PKA-dependent phosphorylation of synaptic proteins exhibited memory-improving effects in various animal models of dementia [37]. PKA, as well as adenylate cyclase, were found in mitochondria.…”
Section: Mitochondrial Target Of Nobiletin's Actionmentioning
confidence: 99%